Theorizing across boundaries: How to conduct a ‘breakout’ literature review - Gruner, Richard L.; Minunno, Roberto (2024)
Best practice advice for literature reviews abounds, yet little advice is available for how to infuse a literature review with theory-generative insights that break out of knowledge silos. To address this issue, we provide guidance on reviewing a range of literature for theory-generative insights through a process of knowledge transfers from a source domain onto a target domain. To do so, mainly building on work concerned with analogical reasoning, we put forward a ‘breakout’ review model, which consists of three iterative stages. While we illustrate the process model in a supply chain management context, we aim to assist any organizational scholar interested in exploring cross-disciplinary literature for new ways of thinking.